Social fiction: an imaginary journey through the Alexandra-Sandton corridor: temporarily subverting everyday acceptance - Wilkinson, Zizke Rolenda (My University, 2017)
ABSTRACT The aim of this dissertation is to explore alternative ways of looking at architecture through the use of theory, the type of theory, alternative building programme development, representing architecture and how architecture is implemented. By doing so, an intervention is designed to expose various social truths, stimulating self reflection and adding value to the Alexandra-Sandton corridor context. This research project utilises the spirit of carnivals as subversive and radical events to change a community’s behaviour. This dissertation explores Bakhtin’s theory of the “carnivalesque”. This theory was used as the theoretical framework based on four characteristics. Throughout the research process these are used to analyse site context and create an intervention. The four carnivalesque characteristics are: - Usurping of hierarchies; - Pushing taboos; - Unusual connections; - Eccentric behaviour. The social inequalities along the Alexandra-Sandton corridor are broken down into every day activities and juxtaposed to amplify and expose hidden rules that we have come to accept in Johannesburg. The intervention acts as a commentary on the future connection of the two contrasting communities for spectacle and self reflection, transcending the everyday experience into a surreal playground through virtual reality and other means. Architecturally, Social Fiction has three main design strands 1. Theoretical exploration; 2. Architecture as emotional stimulus; 3. Virtual reality as fictional representation. Social Fiction is a project that bridges architecture, politics, socioeconomics and philosophy, using the medium of virtual reality and comic book fantasy as an open and accessible way, challenging the traditional plan, section elevation as a means of communication.
Thesis is submitted in partial fulfilment for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Public spaces--South Africa--Sandton; Public spaces--Social aspects--South Africa--Alexandra; Architecture and society--South Africa